A Study on Prevalence and Factors Associated With Obesity among Adolescents in Shivamogga City – A Cross Sectional Study - Kotabal, Rajashree; Chilgod, Nandini; Belur, Mangala N; Nagendra, Kanchana (National Journal of Community Medicine, 2018)
Introduction: Prevalence of obesity in childhood ranges from 5% to 20%. Earlier detection of obesity and its risk factors in children is important to prevent development of complications in adult life. Objectives: To estimate the prevalence and risk factors associated with obesity among adolescents. Methodology: Cross sectional study was conducted for a period of 3 months from July to September 2015 among 13 to 16 years high school children in urban area of Shivamogga city. Sample size was calculated by taking prevalence as 5% and ԑ = 0.35 and sample size was found to be 596. Pretested semi structured questionnaire was used for data collection and anthropometric measurements were recorded as per the WHO guidelines. Results: In the present study prevalence of overweight and obesity were found to be 7.67% and 5.83% respectively. The socioeconomic status, junk food intake, watching TV and playing video/mobile games were found to be statistically significant with the obesity. Conclusion: The prevalence of obesity was high among adolescents in urban area. Study recommends education about the diet and physical activity to adolescents.